Genome-wide identification and expression analysis of the TaRRA gene family in wheat (Triticum aestivum L.) - Sun, Lijing; Lv, Liangjie; Zhao, Jie; Hu, Mengyun; Zhang, Yelun; Zhao, Yun; Tang, Xiaodong; Wang, Peinan; Li, Qianying; Chen, Xiyong; Li, Hui; Zhang, Yingjun (Frontiers in Plant Science, 2022)
Cytokinin is an important endogenous hormone in plants performing a wide spectrum of biological roles. The type-A response regulators (RRAs) are primary cytokinin response genes, which are important components of the cytokinin signaling pathway and are involved in the regulation of plant growth and development. By analysis of the whole genome sequence of wheat, we identified 20 genes encoding RRAs which were clustered into eight homologous groups. The gene structure, conserved motifs, chromosomal location, and cis-acting regulatory elements of the TaRRAs were analyzed. Quantitative real-time polymerase chain reaction (qRT-PCR) results showed that the expression levels of most of the TaRRAs increased rapidly on exogenous cytokinin application. Moreover, the TaRRA family members displayed different expression profiles under the stress treatments of drought, salt, cold, and heat. This study provides valuable insights into the RRA gene family in wheat and promotes the potential application of these genes in wheat genetic improvement.